STRATEGI UMKM USAHA MAKANAN PADA MASA PANDEMI COVID-19 (STUDI KASUS DI KOTA PONTIANAK) - Sulasti, Sulasti - (STIE 'INDONESIA' Pontianak, 2023)
This study seeks to identify priority strategies for MSME food firms in Ponianak City by analyzing internal and external aspects and alternative approaches. Data was collected directly in a survey using cross-sectional data and a qualitative descriptive methodology. The population consists of the 738 owners of all MSME food enterprises in Pontianak City. Associated offices and agencies, banks, village and sub-district officials, BPS, traders, and food entrepreneurs served as the sources for the data. MSME food businesses make up the entire sample of 30 respondents. sampling in an unintentional manner. SWOT and QSPM analysis for strategy evaluation The study's findings suggest that growth and development techniques or aggressive tactics, which emphasize maximizing strength, are alternatives that allow it to be adopted.